Analisis Strategi Pemasaran Produk Industri Kerajinan Kain Tenun Songket Di Desa Pringgasela Kabupaten Lombok Timur - Muhammad, Farhana; Susilawati, Susilawati; Uliya, Rafiza (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2023)
This research aims to determine the strategies used to market the products of the songket woven cloth craft industry in Pringgasela Village by collecting data using observation, interviews and documentation using a descriptive qualitative approach. using the SWOT analysis method. Based on the research results, it is known that the marketing strategy carried out by the Songket Woven Fabric Craft Industry in Pringgasela Village, East Lombok Regency is to maintain the quality of raw materials, as well as woven motifs and patterns. Songket Woven Cloth Craft Product Industry in Pringgasela Village, East Lombok Regency has different prices in terms of the complexity of the pattern. "Based on an analysis of the external environment of the Songket Woven Fabric Industry, an EFAS matrix calculation of 8.5 was obtained. This shows that traditional Pringgaasela songket weaving has a greater opportunity factor than threat factor. Based on the analysis of the internal environment of Pringgasela Traditional songket weaving, the IFAS matrix calculation result was 10.6. "Based on the analysis of the Certesius Diagram, it was found that Pringgasela songket weaving is in the first phase of aggressive growth (grow oriented strategy) so that the alternative strategies implemented by Pringgasela Songket Weaving are market penetration strategies, market development, and maintaining product quality and improving services..